SCHOOL PRINCIPALS’ DIGITAL LEADERSHIP IN ADVANCING TEACHER PROFESSIONALISM AND LEARNING INNOVATION: A QUALITATIVE LITERATURE-BASED ANALYSIS - Tuti Isnani; Uswatun Hasanah; Dewi Cahyani; Moh. Ali (SOSIOEDUKASI, 2026)
The transformation of education in the digital era encourages schools to integrate technology comprehensively into learning practices and institutional management. In this context, the digital leadership of school principals plays a crucial role in directing change, developing teacher professionalism, and creating a sustainable culture of learning innovation. This study aims to analyze the role of principals’ digital leadership in enhancing teacher professionalism and promoting learning innovation in the era of educational transformation. The research method used is a qualitative literature study by analyzing various scientific articles, research reports, and relevant academic documents. The analysis was conducted using thematic content analysis techniques to identify patterns of digital leadership roles and their impact on teachers’ professional practices as well as learning innovation. The results show that principals’ digital leadership contributes through three main aspects: the development of teachers’ digital competencies through training and coaching, the implementation of technology-based academic supervision, and the creation of a collaborative and innovative school culture. In addition, principals are proven to strengthen technology integration in the learning process through a clear digital vision, professional collaboration, and the use of data as a basis for decision-making. However, challenges such as teacher resistance, limited infrastructure, and digital literacy gaps remain major obstacles to optimizing innovation. This study reaffirms the importance of principals’ digital leadership capacity to ensure that educational transformation proceeds effectively and sustainably